More answers

73 − 27 = 46

Q: What is 73 minus 27?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

It is: -73--27 = -46 because a double minus becomes a plus and --27 is the same as +27

The number one rule is "what you do to one side, you must do to the other". So to demonstrate in detail: e - (-73) = -27 e - (-73) + 73 = -27 + 73 e = 46

2,013 minus 1,940 is 73.

73

73

Related questions

It is: -73--27 = -46 because a double minus becomes a plus and --27 is the same as +27

The number one rule is "what you do to one side, you must do to the other". So to demonstrate in detail: e - (-73) = -27 e - (-73) + 73 = -27 + 73 e = 46

558 - 198 - 135 - 73 = 152

70 8-75=-73 3 minus -73=70

2,013 minus 1,940 is 73.

The answer is 57.

55

73

73

73 + 27 = 100

73/n = 27 Therefore, 73/27 = n Therefore, n = 2.703 recurring (that is, 2.703703703...)

4370 minus 27 is 43.